Analysis of Temperature and Residual Stress Distribution in CO2 Laser Welded Aluminum 6061 Plates Using FEM - Numan Mohammed, Sanaa (Al-Khwarizmi Engineering Journal, 2011)
This paper develops a nonlinear transient three-dimensional heat transfer finite element model and a rate independent three-dimensional deformation model, developed for the CO2 laser welding simulations in Al-6061-T6 alloy. Simulations are performed using an indirect coupled thermal-structural method for the process of welding. Temperature-dependent thermal properties of Al-6061-T6, effect of latent heat of fusion, and the convective and radiative boundary conditions are included in the model. The heat input to the model is assumed to be a Gaussian heat source. The finite element code ANSYS12, along with a few FORTRAN subroutines, are employed to obtain the numerical results. The benefit of the proposed methodology is that it offers the capability of optimizing laser welding process, and also provides a reliable estimation of the developed temperatures, as well as the thermal stress (residual stress) and strain fields reducing the experimental effort.